Routine use of automated FiO2 control in Poland: prospective registry and survey - Wilinska, M.; Bachman, T. E.; Piwowarczyk, P.; Kostuch, M.; Tousty, J.; Berła, K.; Hajdar, R.; Skrzypek, M. (Frontiers in Pediatrics, 2023)
Objective: The performance of automated control of inspired oxygen (A-FiO2) has been confirmed in dozens of studies but reports of routine use are limited. Broadly adopted in Poland, our aim is to share that experience. Methods: A prospectively planned observational study of the performance, general use patterns, unit practices, and problems with A-FiO2, based on a web-registry of case reports, complemented by surveys of subjective impressions. Results: In 2019 ninety-two A-FiO2 systems were in routine use in 38 centers. Twenty of the 38 centers had agreed in 2013 to participate in the project. In these centers A-FiO2 was applied in infants of all weights, but some centers restricted it use to weaning from oxygen and unstable infants. A cohort had reported their experience with each use (5/20 centers, 593 cases). A quarter of those infants were managed with a lower target range and three-quarters with alarms looser than European guidelines for manual SpO2 control. The perceived primary advantages of A-FiO2 were: keeping the readings in the target range, reducing exposure to SpO2 extremes, reducing risk from nurse distraction, reducing workload and reducing alarm fatigue. Practices did evolve with experience, including changes in the alarm strategy, indications for use and target range. The potential for over-reliance on automation was cited as a risk. There were a few reports of limited effectiveness (moderate 12/593 and poor 2/593). Conclusions: Automated oxygen control is broadly perceived by users as an improvement in controlling SpO2 with infrequent problems.